2010
DOI: 10.1038/jhg.2010.15
|View full text |Cite
|
Sign up to set email alerts
|

Resequencing of the CCL5 and CCR5 genes and investigation of variants for association with diabetic nephropathy

Abstract: Chemokine (C-C motif) ligand 5 (CCL5) and chemokine (C-C motif) receptor 5 are implicated in the pathogenesis of diabetic nephropathy (DN). We hypothesize that variants in these genes may be associated with DN. The CCL5 and chemokine receptor type 5 (CCR5) genes were resequenced, variants identified (n¼58), allele frequencies determined in 46 individuals (92 chromosomes) and efficient haplotype tag single-nucleotide polymorphisms (htSNPs) selected to effectively evaluate the common variation in these genes. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
3
12
1
Order By: Relevance
“…Some researchers have shown that the CCL5 and CCR5 genes variants could be susceptibility factors for DMI 1,[10][11][12][13][14][15][16] . Yet, the results have not been verified in other studies 3,9,17 . The primary aim of the present study was to derive a more precise evaluation of the associations between the CCL5/CCR5 genes variants and the risk of DMI.…”
Section: Introductioncontrasting
confidence: 78%
See 3 more Smart Citations
“…Some researchers have shown that the CCL5 and CCR5 genes variants could be susceptibility factors for DMI 1,[10][11][12][13][14][15][16] . Yet, the results have not been verified in other studies 3,9,17 . The primary aim of the present study was to derive a more precise evaluation of the associations between the CCL5/CCR5 genes variants and the risk of DMI.…”
Section: Introductioncontrasting
confidence: 78%
“…The heterogeneity disappeared ( I 2 = 0%) after excluding these studies. The trials published by Pettigrew et al ,. Mlynarski et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, 3 were in Caucasian populations while the others were in Asian populations. Additionally, the quality assessment of these studies based on NOS showed that only the article of Pettigrew [ 28 ] had the relative poor quality with 4 scores and the quality the other included studies was good. Table 1 summarized the essential information of all included studies.…”
Section: Resultsmentioning
confidence: 99%